2017
DOI: 10.1038/s41598-017-08036-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep subwavelength ultrasonic imaging using optimized holey structured metamaterials

Abstract: This paper reports the experimental demonstration of deep subwavelength ultrasonic imaging of defects in metallic samples with a feature size of λ/25 using holey-structured metamaterial lenses. Optimal dimensions of the metamaterial’s geometric parameters are determined using numerical simulation and the physics of wave propagation through holey lenses. The paper also shows how the extraordinary transmission capacity of holey structured metamaterials comes about by the coupling of higher frequencies in the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Quadrilateral unit elements were considered for finite element analysis, the unit element size was being kept between λ/12 and λ/24, and the step time was taken as 2e-9. These were set to satisfy the Blake's and CFL (Courant-Friedrichs-Lewy) criterion for mesh size and time-stepping, respectively [14][15][16].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Quadrilateral unit elements were considered for finite element analysis, the unit element size was being kept between λ/12 and λ/24, and the step time was taken as 2e-9. These were set to satisfy the Blake's and CFL (Courant-Friedrichs-Lewy) criterion for mesh size and time-stepping, respectively [14][15][16].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In recent years, the scientific community has seen the rapid development of artificially engineered materials known as metamaterials demonstrating extraordinary possibilities to control electromagnetic [6, 7 ] or acoustic waves [8, 9 ]. Several concepts, such as Phononic crystals [10–14 ], magnifying acoustic hyperlenses [15 ], acoustic super‐lenses [16, 17 ] and metamaterials [18–24 ], have been explored in order to amplify evanescent waves and thereby enable subwavelength resolution. Among the various metamaterial concepts proposed for subwavelength resolution, holey‐structured metamaterials (HSMs) [20 ] are relatively easier to fabricate and exhibit specific properties such as increased transmission or absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various metamaterial concepts proposed for subwavelength resolution, holey‐structured metamaterials (HSMs) [20 ] are relatively easier to fabricate and exhibit specific properties such as increased transmission or absorption. The authors recently demonstrated the application of periodic [21, 22 ] and non‐periodic [23 ] HSM for super‐resolution imaging in the ultrasonic domain. These lenses were shown to help extract the evanescent component of waves scattered by fine defective features in the target specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the frequency of FP-based lens is also limited owing to the requirement that the wavelength should be much higher than the lattice periodicity and hole diameter 20 . Besides this, except refs 14 , 21 , most previous studies in the acoustic regime were based on low frequency. Thus, we studied resonant tunneling and discovered that higher bands of frequency exist for it, which was not possible according to previous works 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%